The Dual Cell Cycle Kinase Inhibitor JNJ-7706621 Reverses Resistance to CD37-Targeted Radioimmunotherapy in Activated B Cell Like Diffuse Large B Cell Lymphoma Cell Lines - Rødland, Gro Elise; Melhus, Katrine; Generalov, Roman; Gilani, Sania; Bertoni, Francesco; Dahle, Jostein; Syljuåsen, Randi G.; Patzke, Sebastian (Frontiers in Oncology, 2019)
The CD37 targeting radioimmunoconjugate 177Lu-lilotomab satetraxetan (Betalutin) is currently being evaluated in a clinical phase 2b trial for patients with follicular lymphoma (FL) and in a phase 1 trial for patients with diffuse large B-cell lymphoma (DLBCL). Herein we have investigated the effect of 177Lu-lilotomab satetraxetan in seven activated B-cell like (ABC) DLBCL cell lines. Although the radioimmunoconjugate showed anti-tumor activity, primary resistance was observed in a subset of cell lines. Thus, we set out to identify drugs able to overcome the resistance to 177Lu-lilotomab satetraxetan in two resistant ABC-DLBCL cell lines. We performed a viability-based screen combining 177Lu- lilotomab satetraxetan with the 384-compound Cambridge Cancer Compound Library. Drug combinations were scored using Bliss and Chou-Talalay algorithms. We identified and characterized the dual-specific CDK1/2 and AURA/B kinase inhibitor JNJ-7706621 as compound able to revert the resistance to RIT, alongside topoisomerase and histone deacetylases (HDAC) inhibitors.